Analisis Isi Sustainable Development Goals tentang Climate Action pada Konten Tiktok @pandawaragroup - Wibisono, Adi; Arviani, Heidy (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
Environmental issues such as pollution, waste, and climate change demand collective awareness. The Sustainable Development Goals (SDGs), particularly Goal 13 (Climate Action), emphasize adaptation, mitigation, and climate literacy. In the digital era, TikTok has proven effective in disseminating sustainability messages. This study analyzes the representation of climate action on the @pandawaragroup account using a descriptive qualitative approach and a case study method. Fifteen videos were purposively selected based on high engagement and relevance to Climate Action indicators. Content analysis was conducted through stages of selection, analysis, interpretation, and conclusion, combined with interactive analysis to understand meaning and social context. The results show that @pandawaragroup’s content aligns with the targets of Climate Action, particularly by depicting environmental crises such as floods caused by waste accumulation, educating the public on waste management, and encouraging community participation in clean-up activities. The representation of climate action is also reflected through collaborations with communities and government institutions in mitigation efforts and environmental preservation campaigns. The use of simple and emotional communication effectively raises awareness among younger generations, expands sustainable public advocacy, and encourages community participation in local environmental actions.